Development of a greenhouse roof cleaner (2011)
The efficiency of a greenhouse is influenced by the cleanliness of the glazing material through which heat and light penetrate into the enclosure. The common cleaning method for most greenhouses in developing countries is the use of a ladder to climb onto the roof to clean which is labour intensive, time-consuming, imposes severe loads on the roof that could cause failure and is dangerous to the cleaner. Consequently, many greenhouse roofs are rarely cleaned and the accumulated dirt reduce the amount of light and heat penetrating into the house. Experimental studies in such greenhouses may fail to produce valid findings while crop production may not yield the desired produce. There is therefore the need for appropriate equipment for effective cleaning of greenhouse roofs in order to eliminate the disadvantages of the existing common method. The focus of this study was to develop simple equipment that could be used for the cleaning of a greenhouse roof. A manually operated brush type greenhouse roof cleaner was designed, fabricated and tested. The equipment consisted of a roughly cylindrical brush mounted on a frame attached to a handle made of three concentric and adjustable cylindrical pipes. The equipment was fitted with a wash mix dispenser operated by a 1 hp sump pump. The equipment testing involved recording the illumination within and outside three greenhouses before and after washing with the equipment. Increases of 6.03, 13.19 and 16.36 % in transmittances of the roofs following washing with the equipment were recorded. A simple, easy to set-up, operate and maintain equipment for the cleaning of greenhouse roof has been designed and demonstrated great potentials in cleaning. Further studies aimed at reducing the weight, prolonging service life and improving efficiency are required.